Effect of Learning Curve in Transradial Approach to Coronary Angiography and Percutaneous Intervention - Mahmood Zaidan, Saad; Zaidan Ammran, Ammar; Jubran Khaleel, Zakariya (Diyala Journal of Medicine, 2020)
Background: TR approach is suitable for most patient and limitations is very low. It become more popular and approved in international guidelines because of increase success rate and low complication rate and low cost. There is also parallel advancement in instruments used in TR approach. Objective: To establish the rule of learning curve in transradial approach to CA and PCI and encourage the operator for doing more transradial catheterization. Patients and Methods: Patients admitted for CA or PCI. Data collected from patient and procedure including age, sex, contrast volume, total procedure time. flouro time, radial artery spasm and number of cases that transformed to femoral. We divided the study in two groups: group A first half of patient and group B the second half. Results: Total numbers of patients (139) and there age ranging from 28 to 80 years (mean of 55.13). Number of males 131 (94.2%) and females 8 (5.7%).The mean value of contrast volume used in group A that underwent CA, ad hoc and PCI ,(was 63.10,124.20 and 106.91 ml) respectively and for group B (50.07,88.19 and 49.56 ml).The mean total time of procedure of group A underwent CA, ad hoc and PCI was (17.16,24.9 and 26.13 minutes) respectively and for group B(13.66,26.3 and 16.4 minutes).The mean fluorotime of group A underwent CA, ad hoc and PCI was (4.61,7.2 and 6.62 minutes) and for group B (3.06,7.32 and 3.51 minutes ). Seventeen case subjected to radial artery spasms divided into 11 cases (15.7%) in group A and 6 cases (8.69 %) in group B. There were 8 cases (11.4 %) of group A transferred to femoral approach and 4 cases (5.79 %) of group B transferred to femoral access. Conclusion: There was much benefit from the effect of learning curve in doing TR approach to CA and PCI.